2005
DOI: 10.1352/0895-8017(2005)110<216:piaoaw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Inpatient Admissions of Adults With Intellectual Disabilities: Predictive Factors

Abstract: Information on admission to psychiatric inpatient units is lacking from the literature on contemporary services for people with intellectual disability and mental health needs. Here we report on predictors of admission for a cohort of 752 adults from this population living in community settings; 83 were admitted. We also report on two subsamples of this cohort for whom different psychometric measures concerned with psychiatric symptoms and behavior had been completed. Schizophrenia spectrum disorders and mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 13 publications
2
38
2
Order By: Relevance
“…Contrary to expectations, the presence of physical aggression or destruction of property were not related to ED visits, even though past research has associated these externalizing behaviors with hospitalization (Cowley et al, 2005) and considerable parent distress (Minnes, Woodford, & Passey, 2007). The presence of physical aggression to others did emerge as the most frequent type of crisis across groups, and the fact that it was not related to ED use suggests that emergency service engagement may not be a defining feature of crisis in the context of family care.…”
Section: Individuals With Intellectual 12contrasting
confidence: 76%
See 1 more Smart Citation
“…Contrary to expectations, the presence of physical aggression or destruction of property were not related to ED visits, even though past research has associated these externalizing behaviors with hospitalization (Cowley et al, 2005) and considerable parent distress (Minnes, Woodford, & Passey, 2007). The presence of physical aggression to others did emerge as the most frequent type of crisis across groups, and the fact that it was not related to ED use suggests that emergency service engagement may not be a defining feature of crisis in the context of family care.…”
Section: Individuals With Intellectual 12contrasting
confidence: 76%
“…Emergency response to a psychiatric crisis suggests that the event is related to a mental health and behavioral issue. Indeed, the presence of psychiatric or medical symptoms, and of aggressive behavior toward self or other, are the most commonly cited contributors to accessing mental health services (Cowley, Newton, Sturmey, Bouras, & Holt, 2005;Davidson et al, 1994;Edelstein & Glenwick, 1997;Lunsky et al, 2008), and psychiatric issues are consistent drivers of hospitalization in this population (Balogh, Hunter, & Ouellete-Kuntz, 2005;Lunsky & Balogh, 2010). Little research exists specifically examining these variables in the context of family care, however.…”
Section: Individuals With Intellectualmentioning
confidence: 99%
“…It was primarily this group who experienced restraint in the ED. Similar to Cowley et al (2005), visits involving physical aggression were more likely to result in admission. That being said, 35% of visits involving physical aggression did not result in admission.…”
Section: Discussionmentioning
confidence: 98%
“…Comparable to related research on predictors of hospital admission (Cowley, Newton, Sturmey, Bouras, & Holt, 2005), the most common reason for families bringing their family member with ID to the ED was physical aggression. It was primarily this group who experienced restraint in the ED.…”
Section: Discussionmentioning
confidence: 98%
“…Being diagnosed with a schizophrenia spectrum condition increases the likelihood of having a psychiatric admission over people with other psychiatric diagnoses (Cowley et al 2005). Moreover, a study conducted in Taiwan found that hospital admissions for people with ID and co-occurring schizophrenia cost more than admissions for people with ID and other mental illnesses (Lai et al 2011).…”
Section: Service Provisionmentioning
confidence: 99%